Lake level evidence for a mid-Holocene East Asian summer monsoon maximum and the impact of an abrupt late-Holocene drought event on prehistoric cultures in north-central China. (April 2023) - Zhang, Zhiping; Shen, Zhongwei; Zhang, Shanjia; Chen, Jie; Chen, Shengqian; Li, Dongxue; Zhang, Shuai; Liu, Xiangjun; Wu, Duo; Sheng, Yongwei; Tang, Qiuhong; Chen, Fahu; et al.
Uncertainty regarding the timing of the highest Holocene water level of enclosed Dali Lake in northern China has led to controversy about whether the East Asian summer monsoon (EASM) peaked in the early Holocene or the mid-Holocene. Therefore, a record combining a reliable chronology with unambiguous lake level indicators is essential to resolve the issue. In this study, we established a temporal sequence of well-preserved paleolake shorelines at different elevations around Dali Lake using quartz optically stimulated luminescence (OSL) dating. Combining the new OSL-based chronological data with the previously published ages of beach ridges, we constructed an integrated lake level record for Dali Lake since the last deglaciation; the record is chronologically well-constrained and provides a clearer representation of lake level changes than previous studies. The main findings are as follows: (1) the level of Dali Lake rose gradually during 14.5–8.0 ka and reached a highest level during 8.0–6.0 ka that was 61 m higher than today, before gradually declining after 6.0 ka; (2) although the short-lived highstand of Dali Lake during the early Holocene was caused by both monsoon precipitation and snow/ice meltwater influx, the mid-Holocene lake level maximum was mainly the result of increased monsoon precipitation. These findings indicate that the EASM maximum in the region occurred during the mid-Holocene, which is supported by precipitation-proxy records from the EASM margin; (3) a major decline ( 30 m) of the level of Dali Lake occurred at 4.2 ka, reflecting a regional-scale drought event in northern China. Combined with near-contemporaneous frequent floods in the lower Yellow River, we propose that the pattern of "drought in northern China, flooding in central China" occurred during 4.2–3.8 ka, triggering the migration of the prehistoric human population of the area to the central Plain of China. This population migration may have destabilized the existing social order and promoted the emergence of more complex societies, leading to the development of early civilization in north-central China.